Mental health status of healthcare workers in COVID-19 vs non-COVID-19 units: findings from Shariati Hospital, Tehran - Abdolhakim Jorbonyan; Maryam Khosrozadeh; Ali Karimi-rozveh (Intelektual Pustaka Media Utama, 2026)
This cross-sectional study compared the mental health status of healthcare workers in COVID-19 and non-COVID-19 wards at Shariati Hospital, Tehran, Iran. A total of 250 healthcare workers were selected via systematic random sampling and completed the 28-item General Health Questionnaire (GHQ-28). Data were analyzed using descriptive and inferential statistics in SPSS 24.0. Participants had a mean age of 35.5 years (SD = 8.28) and included 52.6% females and 47.4% males. Based on a GHQ score >23, 63 (53.3%) of staff in COVID-19 wards and 51 (44.7%) in non-COVID-19 wards were suspected of having some degree of mental health disorder. Independent t-test results indicated that healthcare workers in COVID-19 wards experienced significantly higher levels of general mental health problems (t = 4.20, P < 0.001), anxiety (t = 5.55, P < 0.001), and somatic symptoms (t = 4.09, P < 0.001) compared to their counterparts in non-COVID-19 wards. The study highlights a relatively high prevalence of mental health disorders among hospital staff, particularly those working in COVID-19 units. Early identification of at-risk personnel, implementation of targeted interventions, and provision of counseling and psychological support are essential to safeguard the mental well-being and performance of healthcare workers during the ongoing pandemic.